Scientific Approaches to the Study of State Regulation Mechanisms for Environmental Safety Ensuring in Ukraine - Biryukov , Vadim (Theory and Practice of Public Administration, 2019)
Modern environmental policy has a need for the practical implementation of scientic approaches to ensuring environmental safety in Ukraine. In particular, during the reformation of the environmental protection system attention should be paid to the improvement of managerial, structural, organizational and regulatory activities in the  eld of management of natural resources and harmonization of environmental interests of the society with its economic interests. The reforms being implemented in the framework of European integration processes are intended to change the state’s participation in economic activity, namely, to adjust the economic system to choose the most effective options for the conservation and use of natural resources, taking into account the experience of foreign countries. In Ukraine, as in all civilized countries, the priority national interest is the provision of environmental safety in the face of potential and actual natural disasters, accidents and disasters. The ful llment of this vital task at the present stage in the ecological sphere has become unprecedented in our country. In our opinion, the mechanisms of state regulation in the provision of environmental safety should be implemented at the legislative level, by adopting such laws that would enable the executive authorities to take managerial decisions with reference to scienti cally sound norms of the impact of economic and other activities on the environment by putting into effect the regulatory -legal and methodological documents.The environmental protection system reform for our state is a step forward, because the low level of implementation of the environmental policy of Ukraine and the rejection of important environmental laws may lead to irreparable consequences. A prerequisite for ensuring environmental safety and the sustainable use of natural resources in the  eld of environmental protection in Ukraine should be a clear de nition of the relevant specialized system of state supervision and control by creating a single environmental authority and ensuring a guaranteed level of security that corresponds to the level of developed countries of the world. In our opinion, the codi cation of environmental legislation will provide an opportunity for effective state management in the  eld of environmental protection and will ensure the fundamental rights of citizens and society.